2011
DOI: 10.1002/jbm.a.33004
|View full text |Cite
|
Sign up to set email alerts
|

Hemocompatibility of titania nanotube arrays

Abstract: We regret any confusion caused by this error.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
11
0

Year Published

2011
2011
2015
2015

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(11 citation statements)
references
References 0 publications
0
11
0
Order By: Relevance
“…It was our aim to examine which diameter of NTs is more appropriate for protein binding and more suitable (long-term) as nanostructured implant material. Implanted material in contact with blood becomes adhered to plasma proteins 13,76 once embedded in the body. 13 Plasma is rich in proteins, carbohydrates, and lipids, as well as lipoprotein and other combinations of complexes; however, when studying clinically relevant proteins, our aim was to first determine their interactions with NTs' surfaces.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…It was our aim to examine which diameter of NTs is more appropriate for protein binding and more suitable (long-term) as nanostructured implant material. Implanted material in contact with blood becomes adhered to plasma proteins 13,76 once embedded in the body. 13 Plasma is rich in proteins, carbohydrates, and lipids, as well as lipoprotein and other combinations of complexes; however, when studying clinically relevant proteins, our aim was to first determine their interactions with NTs' surfaces.…”
Section: Discussionmentioning
confidence: 99%
“…Previous reports have shown binding of different protein or peptide interlayers, such as growth factors, 18 albumin, fibrinogen, IgG, 13,19 fibronectin, 20 collagen type 1, 21 BMP-2, 18,22 RGD peptide, 23 and laminin-derived peptide, 24 to TiO 2 nanotubes (NTs), which could provide for crucial information concerning their integration into the body. The majority of the more recent investigations studied the combination of different cell types with different prebound proteins 25,26 on TiO 2 NTs and found that binding is cell-specific and cannot be generalized.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations